Energy-sustainable hospitals: Integration of a novel compound parabolic concentrator system with two storage tanks for domestic hot water production at high and low temperatures. (25th February 2023) - Matera, Nicoletta; Mazzeo, Domenico; Congedo, Paolo Maria
Highlights: A novel solar concentrating system for domestic hot water production in hospitals. High- and low-temperature users are supplied from two storage tanks and two boilers. A transient tool for evaluating the system size effect on thermal behaviour was built. To detect the best system configuration, different yearly indicators were analysed. Like the f-chart method, empirical correlations of the solar fraction were proposed. Abstract: Hospital buildings are known to be energy-intensive, since they are operated all year round at high costs, contain sophisticated medical equipment, and follow strict cleaning practices and environmental regulations. Domestic hot water consumption accounts for most of the energy consumption in hospital buildings. The objective of this research work is to study the energy performance of a novel compound parabolic concentrator system connected to two heat exchangers arranged in series, in turn, connected to two storage tanks that supply domestic hot water to two different hospital users. The first user requires high temperatures for laboratories, cleaning, sterilization of operating room instruments, and so on, while the second user requires lower temperatures mostly represented by health services. To guarantee the supply of the thermal energy needs, an external integration system was connected to each storage tank. A calculation scheme was created in a transient simulation environment that provides dynamically all temperatures at the output of the various system components and all thermal exchanges through each component. Starting from a reference configuration, a parametric simulation was carried out by varying the size of the plant components. The research aim was to evaluate the influence of the component sizes on the plant's transient behaviour by means of a qualitative-quantitative determination of the monthly and yearly system energy exchanges and some performance indicators, such as the solar fraction, solar efficiency and fuel consumption on a monthly and yearly basis. The outcomes of this research demonstrated that the choice of the storage tank volumes and the secondary circuit flow rate allows designers to allocate the solar energy produced between the two users, while the collector area and the primary circuit flow rate allow designers to fix the fraction of overall thermal demand to be satisfied and the efficiency of solar energy conversion into thermal energy to the fluid. Finally, similarly to the f-chart method, some empirical correlations are proposed to rapidly verify the system performance without using any transient simulation tool.